2002
DOI: 10.1038/sj.bjc.6600530
|View full text |Cite
|
Sign up to set email alerts
|

Childhood solid tumours in relation to infections in the community in Cumbria during pregnancy and around the time of birth

Abstract: In a retrospective cohort study of all 99 976 live births in Cumbria, 1975Cumbria, -1992, we investigated whether higher levels of community infections during the mother's pregnancy and in early life were risk factors for solid tumours (brain/spinal and other tumours), diagnosed 1975 -1993 under age 15 years. Logistic regression was used to relate risk to incidence of community infections in three prenatal and two postnatal quarters. There was an increased risk of brain/spinal tumours among children exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…It is unclear whether this seasonal variation of births in CNS tumour reflects variations in exposure to specific infections, variable levels of the burden of community infections or other factors. Some studies have suggested that exposure to infections of the mother or the child around the time of birth may be associated with increased risk of certain CNS tumours in children (Linet et al, 1996;Linos et al, 1998;Dickinson et al, 2002;McNally et al, 2002). In addition, three polyomaviruses have shown oncogenic properties when injected into the brain of newborn laboratory animals (White et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this seasonal variation of births in CNS tumour reflects variations in exposure to specific infections, variable levels of the burden of community infections or other factors. Some studies have suggested that exposure to infections of the mother or the child around the time of birth may be associated with increased risk of certain CNS tumours in children (Linet et al, 1996;Linos et al, 1998;Dickinson et al, 2002;McNally et al, 2002). In addition, three polyomaviruses have shown oncogenic properties when injected into the brain of newborn laboratory animals (White et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…CTCTGCGAGAATCCCGAGTGGGCACCATTGAAGGATAA 338 ************************************** considered an oncogenic virus, several reports have suggested an epidemiological association not only between MV and brain tumours but also with HD (Dickinson et al, 2002;Tyari et al, 2003).…”
Section: Hd-134mentioning
confidence: 99%
“…An infectious aetiology of CNS tumours is supported by ecological studies of space -time clustering (McNally et al, 2002) and seasonal variation of births, with an excess of patients with different subgroups of CNS tumours being born during winter and fall (Yamakawa et al, 1979;Hoffman et al, 2007;Schmidt et al, 2009), although results are inconclusive. Further observational studies indicate that infection during pregnancy (Linos et al, 1998;Fear et al, 2001;Dickinson et al, 2002) or during the neonatal period (Linet et al, 1996) might be associated with an increased risk for CNS tumours; however, evidence is limited and results are inconsistent (McKinney et al, 1999).…”
mentioning
confidence: 99%